The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1590/0100-67622016000300015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Time Management in Modeling of Curve Resistance to the Penetration of a Latosol Under Different Uses and Management of Pastures and Native Woodland

Abstract: The soil resistance to penetration study helps in understanding the state of soil compaction, indicating how best to manage it. The present study aimed to verify the influence of time management in modeling curves of resistance to penetration in Oxisol under different uses and management of pastures and woodland in field conditions, using the stepwise procedure. The study was conducted in the Cerrado region. Five (5) systems of uses and management of pastures and native woodland were evaluated: ILPF: crop-live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The critical density values found for sandy soils under agricultural use are cited and range from 1.6 to 1.8 [19], well above that found in this study. This lower soil density in the upper layer (0-5 cm) was found in studies in natural forests [19,30,31]. This general pattern of natural or anthropic soils is caused by the greater intake of organic matter in the most superficial layer of the forest soil.…”
Section: Tablesupporting
confidence: 61%
See 1 more Smart Citation
“…The critical density values found for sandy soils under agricultural use are cited and range from 1.6 to 1.8 [19], well above that found in this study. This lower soil density in the upper layer (0-5 cm) was found in studies in natural forests [19,30,31]. This general pattern of natural or anthropic soils is caused by the greater intake of organic matter in the most superficial layer of the forest soil.…”
Section: Tablesupporting
confidence: 61%
“…The lowest soil density in areas occupied by native forests has already been found in different Brazilian Biomes [15,17,19,[30][31][32][33][34][35][36][37]. In the same watershed, Flores et al [32] found in Argissolo Vermelho, that the density of native forest and native field soil was lower than in the cultivation areas, with greater differences in the layer of higher organic matter intake (0 a 0.05 m).…”
Section: Tablementioning
confidence: 86%
“…Most researches have focused on studying a particular integrated system, with only eight out of the 92 papers studying two systems (no paper studied more than two integrated systems). These include studies about both integrated crop–livestock and integrated crop–livestock–forest systems (Bieluczyk et al., 2020; Fernandes et al., 2016; Guardiola et al., 2017; Nascimento et al., 2019; Sousa Neto et al., 2014) and integrated crop–livestock and integrated livestock‐forest systems (Damian et al., 2020; Hilimire et al., 2013; Silva et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Fernandes et al. (2016) found that the integrated systems (crop–livestock and crop–livestock–forest) promoted better soil physical quality by assessing soil bulk density, resistance to penetration, total porosity and soil organic matter down to 40 cm during one year in a Ferralsol.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of integrated agricultural systems have often been compared to preserved areas, and the BD is sensitive to changes in the soil physical characteristics because this attribute is considered a good indicator of soil quality. BD is directly associated with other important soil attributes, including penetration resistance, macroporosity, and water infiltration (Cunha et al, 2011;Panachuki et al, 2011;Fernandes et al, 2016). Although the iCLF, EF, and PF used mechanized systems, BD did not change in these areas.…”
Section: Discussionmentioning
confidence: 99%